A New Sodium-ion-conducting Layered Perovskite Oxide as Highly Active and Sulfur Tolerant Electrocatalyst for Solid Oxide Fuel Cells. (February 2019) - Qu, Jifa; Wang, Wei; Xu, Xiaomin; Zhong, Yijun; Song, Yufei; Yang, Guangming; Zhou, Wei; Shao, Zongping
Abstract: In this paper, a layered perovskite oxide NaLaTiO4 with sodium-ion conductivity is proposed as a highly active, sulfur tolerant and stable anode for solid oxide fuel cells (SOFCs). The cell with NaLaTiO4 -infiltrated samaria-doped ceria (SDC) anode shows high power outputs and favorable stability over 200-hour operation with 1000 ppm H2 S-H2 as fuel at 800 o C. The excellent sulfur tolerance of NaLaTiO4 is attributed to its polarity, high surface basicity, oxygen vacancy concentrations and water storage capability. These results may open up new avenues for the design of high-performance, sulfur-tolerant anodes for SOFCs.